"Bowing Technique" for Using a HeartMate 3 Mini-Apical Cuff. Issue 4 (11th March 2022) - Ohira, Suguru; Grunfeld, Matan; Levine, Avi; De La Pena, Corazon; Spielvogel, David; Kai, Masashi
Abstract : A HeartMate 3 mini-apical cuff is designed to facilitate minimally invasive left ventricular assist implantation. A possible problem of using a mini-apical cuff is that multiple buttress braided sutures can interfere with a HeartMate 3 pump when locking the pump. If this happens in a minimally invasive approach, multiple manipulations to engage the pump can cause catastrophic myocardial injury and uncontrollable bleeding, especially in patients with a fragile myocardium. We are reporting a simple and effective technique to prevent suture jamming in the setting of mini-apical cuff implantation utilizing multiple buttress sutures.